Performance investigation and enviro-economic analysis of active vertical solar distillation units. (1st May 2015) - Sharon, H.; Reddy, K.S.
Abstract: In this work, performance enhancement of vertical still by active mode operation was carried out using mathematical modeling. The reported model is validated with the mass transfer model that is usually employed for prediction of mass transfer in vertical stills. The two configurations considered for active mode operation are CVDS (cascaded vertical-double slope) still and CVSS (cascaded vertical-single slope) still. The optimum absorber area and gap between condensing and evaporating surface is 4 m 2 and 0.20 m, respectively. Effect of shade on system performance has also been reported. CVDS and CVSS unit produces nearly 25.63% and 13.33% higher distillate than the passive vertical still of similar dimensions. The yield is found to decrease by 10% for every 5% increase in salinity of feed. Maximum yield of 24.06 kg/d is recorded for CVDS unit during the month of April. CVDS unit has maximum energy payback period of 2.25 years and can mitigate at least 69.85 tons of CO2 emission during its life time of 20 years and can provide distilled water at 34.3 USD/kL or less. High yield, low water production cost and less ground area occupancy make the unit more feasible and competitive for rural and urban applications. Highlights: Optimization of Cascaded vertical-single slope vertical-double slope stills. Investigation of year round performance analysis of solar stills. Environmental and Economic analysis of active solar stills. Solar desalination for potable water in rural and urban areas.